Managerial for Schools in Rising The Etos Of Educational Energy Work in SMPN 02 Bandar Mataram Lampung Tengah - Lukman Abdul Majid (Tahta Media Group, 2023)
The principal's managerial skills are instrumental in determining the success of the school's education programme. Principals need to be able to fulfil their roles as educators, managers, administrators, supervisors, leaders and motivators, which require special skills and a deep understanding of school dynamics. Research at SMPN 02 Bandar Mataram shows that the principal has succeeded in carrying out his role well, so that school management runs effectively, despite facing challenges from the work ethic of education personnel. These challenges come from internal factors, including cultural diversity, educational, economic and social backgrounds, as well as external factors, such as work wages, work climate, attitude cultivation and time allocation. In overcoming these obstacles, principals strengthen communication and cooperation among education personnel, and increase their motivation and commitment to their duties and responsibilities. The right approach creates a conducive work environment, which in turn improves the work ethic of education personnel. The positive impact of these efforts can be seen in the achievement of educational goals at the school, ensuring that planned programmes can run optimally and deliver the expected results.